Hematopoietic cell transplantation in severe combined immunodeficiency: The SCETIDE 2006-2014 European cohort - Lankester, Arjan C; Neven, Benedicte; Mahlaoui, Nizar; von Asmuth, Erik G J; Courteille, Virginie; Alligon, Mikael; Albert, Michael H; Serra, Isabelle Badell; Bader, Peter; Balashov, Dmitry; Beier, Rita; Bertrand, Yves; et al. (Journal of allergy and clinical immunology, 2022)
BACKGROUND: Hematopoietic stem cell transplantation (HSCT) represents a curative treatment for patients with severe combined immunodeficiency (SCID), a group of monogenic immune disorders with an otherwise fatal outcome. OBJECTIVE: We performed a comprehensive multicenter analysis of genotype-specific HSCT outcome, including detailed analysis of immune reconstitution (IR) and the predictive value for clinical outcome. METHODS: HSCT outcome was studied in 338 patients with genetically confirmed SCID who underwent transplantation in 2006-2014 and who were registered in the SCETIDE registry. In a representative subgroup of 152 patients, data on IR and long-term clinical outcome were analyzed. RESULTS: Two-year OS was similar with matched family and unrelated donors and better than mismatched donor HSCT (P < .001). The 2-year event-free survival (EFS) was similar in matched and mismatched unrelated donor and less favorable in mismatched related donor (MMRD) HSCT (P < .001). Genetic subgroups did not differ in 2-year OS (P = .1) and EFS (P = .073). In multivariate analysis, pretransplantation infections and use of MMRDs were associated with less favorable OS and EFS. With a median follow-up of 6.2 years (range, 2.0-11.8 years), 73 of 152 patients in the IR cohort were alive and well without Ig dependency. IL-2 receptor gamma chain/Janus kinase 3/IL-7 receptor-deficient SCID, myeloablative conditioning, matched donor HSCT, and naive CD4 T lymphocytes >0.5 × 10e3/μL at +1 year were identified as independent predictors of favorable clinical and immunologic outcome. CONCLUSION: Recent advances in HSCT in SCID patients have resulted in improved OS and EFS in all genotypes and donor types. To achieve a favorable long-term outcome, treatment strategies should aim for optimal naive CD4 T lymphocyte regeneration.
Keywords: Cohort Studies; transplantace hematopoetických kmenových buněk; nepříbuzný dárce; Severe Combined Immunodeficiency; těžká kombinovaná imunodeficience; Hematopoietic Stem Cell Transplantation; příprava pacienta k transplantaci; Transplantation Conditioning; Unrelated Donors; lidé; Humans; kohortové studie